2018
DOI: 10.1002/ccd.27578
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous coronary artery originating from the opposite sinus of Valsalva (ACAOS), fractional flow reserve‐ and intravascular ultrasound‐guided management in adult patients

Abstract: Conservative treatment may be justifiable in adult patients with ACAOS in the presence of normal FFR and nonsuspicious symptoms, despite the presence of an interarterial course and/or slitlike orifice on IVUS. We recommend the use of FFR and IVUS in the standard work-up for adult patients with ACAOS and propose the use of a flowchart to aid in decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 23 publications
(39 reference statements)
1
43
0
Order By: Relevance
“…In our opinion, the systematic evaluation of the CAD, including the calcification score and stenosis severity according to the respective guidelines, as well as the downstream investigations including exercise testing, perfusion imaging, and catheter angiogram, et al is a priority in CAD patients, whereas a meticulous review of the patients' anatomical features is needed to exclude coronary anomaly, especially when handling patients with CAD symptoms of higher severity than those expected from the plaque itself. Recently, Driesen, et al reported the value of fractional flow reserve (FFR) in better assessing the hemodynamic level of patients with ACAOS, which undoubtedly provided a new method to identify the patients at risk and helped with clinical decision making for patients with ACAOS [25].…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, the systematic evaluation of the CAD, including the calcification score and stenosis severity according to the respective guidelines, as well as the downstream investigations including exercise testing, perfusion imaging, and catheter angiogram, et al is a priority in CAD patients, whereas a meticulous review of the patients' anatomical features is needed to exclude coronary anomaly, especially when handling patients with CAD symptoms of higher severity than those expected from the plaque itself. Recently, Driesen, et al reported the value of fractional flow reserve (FFR) in better assessing the hemodynamic level of patients with ACAOS, which undoubtedly provided a new method to identify the patients at risk and helped with clinical decision making for patients with ACAOS [25].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac catheterization can be performed if noninvasive testing is non diagnostic and if there is suspected coronary artery disease [12]. Furthermore, intravascular ultrasound (IVUS) and fractional flow reserve (FFR) is increasingly being performed and these are highly sensitive to depict the exact anatomy and stenotic severity [13].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the current article erroneously state that, “dynamic testing and detailed assessment of anatomico‐functional features like an intramural course and quantifying severity of stenosis is not possible,” with non‐invasive imaging but this is not accurate. Identification of an intramural segment and the angle of origin, which are closely associated with the “slitlike orifice” feature they highlight, can be delineated with computed tomography, so it is not clear that IVUS offered unique insight . In the current series, 12 patients (2 with anomalous left and 10 with anomalous right CA origin) were recommended to undergo intervention, 7 with an FFR ≤0.80 (1 left, 6 right), including 6 with a slitlike orifice and 4 with bona fide symptoms (the patient without a slitlike orifice had an FFR of 0.80 and atypical symptoms).…”
mentioning
confidence: 86%
“…However, in younger patients it is important to ask what we will learn and how it will change management. Noninvasive imaging is most often the means by which an AAOCA is first detected, and cardiac computed tomography can provide outstanding and thorough anatomic resolution . The authors of the current article erroneously state that, “dynamic testing and detailed assessment of anatomico‐functional features like an intramural course and quantifying severity of stenosis is not possible,” with non‐invasive imaging but this is not accurate.…”
mentioning
confidence: 96%